Dermal fillers - Goldberg, David J. (Aesthetic dermatology / series editor D.J. Goldberg, 2018)
The aging process affects every aspect of the body, with the face being one of the first places to show signs. The search for the perfect injectable filler has taken an interesting path with the majority of innovations having been introduced in the last 30 years. The patient-driven demand for safe and effective minimally invasive aesthetic procedures has led to the development of an expanding and competitive market for dermal fillers. The demand for soft tissue augmentation has grown rapidly since its start in 1981 with collagen fillers. Fillers using hyaluronic acid, calcium hydroxyapatite, poly-L-lactic acid, and polymethylmethacrylate provide a wide range of options so that the best cosmetic outcome can be attained. The ability to correct facial rhytides and folds, to augment lips and cheeks, to correct acne scars, and now even to replenish volume loss in the dorsum of the hands is something that many practitioners thought would never be possible. This publication reviews the history of fillers, injection techniques, complications and safety as well as the novel use of fillers and fillers of the future.